2013
DOI: 10.1017/s0007114512005946
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental education and adolescents' soft drink intake from the age of 11–13 years, and possible mediating effects of availability and accessibility

Abstract: The present study examined the prospective relationship between parental education and adolescents' soft drink intake over 20 months, and possible mediating effects of adolescents' availability and accessibility of soft drinks at home. A total of 866 adolescents, with data on two time points in the Norwegian HEalth In Adolescents (HEIA) cohort study , were included in the analyses. Data on intake and determinants of soft drinks were collected from adolescents and both parents by questionnaires. Mediation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 36 publications
(55 reference statements)
2
28
0
3
Order By: Relevance
“…The search output provided 8,464 studies for eligibility review after removal of duplicates, of which 8,417 studies were excluded upon review of titles and abstracts. From 47 studies eligible for the full‐text review process, 27 studies were excluded, yielding an eligible 20 studies for the final review (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search output provided 8,464 studies for eligibility review after removal of duplicates, of which 8,417 studies were excluded upon review of titles and abstracts. From 47 studies eligible for the full‐text review process, 27 studies were excluded, yielding an eligible 20 studies for the final review (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review tested potential predictors at the intrapersonal, interpersonal, and organizational/community levels for their mediating role in the association between SEP and dietary behaviours (Table ). Accordingly, eleven studies, seventeen studies, and three studies assessed mediators at the intrapersonal level, interpersonal level, and organizational/community level, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the association between SES and food habits among Norwegian adolescents might be different if the FAS were to be replaced with an indicator that taps other dimensions of the SES construct than material wealth. Soft drink consumption, for example, is associated with SES among Norwegian adolescents in studies that use parental education [29,30,69], parental occupation [28] or cultural capital [25] as indicators of SES. It is likely that soft drinks are less influenced by material wealth as it is relatively cheap compared to other food items in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…However, many schoolchildren fall short of these recommendations [19–24]. Poor diet is of particular concern with regard to adolescents living in families of low socio-economic status (SES), because adolescents of low SES eat less fruit and vegetables [20,2528] and more sugar-added food items [24,29,30] than their high SES counterparts. Based on this background, initiatives to improve and equalize young people’s food habits receive high priority in most Western countries [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies among various Dutch samples have shown means of nine to ten EDSF events per week (17,18) . Children from low socio-economic backgrounds have been found to be at risk for high EDSF and EDD consumption (19,20) . Differences in intakes between boys and girls and age groups have also been investigated (12,15,21) , but results are contradictory.…”
mentioning
confidence: 99%